Efektivitas Expressive Writing terhadap Penurunan Tingkat Kecemasan pada Mahasiswa Psikologi Angkatan 2022 Kelas K Universitas Negeri Padang - Rahmayati, Septi; Nusaibah, Tsabitha; Ramadhani, Annisa; Zikra, Muhammad Al; Adhani, Reihan Lutviansyah; Aulia, Prima (MASALIQ, 2024)
The research was conducted to see if expressive writing techniques are effective for reducing anxiety. And also can overcome excessive anxiety that exists in individuals. Data collection is carried out using expressive writing techniques during the technique process. This research is a quasi-experiment in the form of a one group pre test, post test design. The expressive writing technique was carried out for four days with 5 research subjects who were psychology students of class 2022, class K, Padang State University. The subjects were measured using a pre test, then given treatment, then given a post test to see if this expressive writing technique is effective for students who experience anxiety. The data obtained were then analyzed using a paired sample t-test with the results obtained a significance value of 0.000 < Cronbach's alpha (0.05). It can be seen that the results of the study show that the expressive writing technique is said to be effective for reducing the anxiety of psychology students class 2022 class K State University of Padang. Research participants also know how to overcome anxiety in the future if anxiety arises. Participants in this study can also perform expressive writing techniques independently. based on the results of this study, it is recommended that subjects can convey their opinions to provide advice to researchers about input that should be used as lessons for researchers.